Impact of population‐specific dental development on age estimation using dental atlases. Issue 1 (4th December 2018) - Adams, Donovan M.; Ralston, Claira E.; Sussman, Rachel A.; Heim, Kelly; Bethard, Jonathan D.
Abstract: Objectives: The steady development and subsequent eruption of the dentition is particularly useful for the estimation of age in juveniles. There are few studies that examine and test methods on a population‐diverse sample. Our goal is to test the Ubelaker (1989 ) and London Atlas (2010) dental charts on a sample representing several different population backgrounds to infer if refinement for population‐specific standards should be developed. Materials and methods: The first and second authors examined panoramic radiographs of 335 individuals from the James K. Economides Orthodontic Collection blind to chronological age, sex, and ancestry and scored using both dental atlases. Results: The age of Native Americans and African Americans was generally overestimated, suggesting faster rates of development. European Americans and New Mexico Hispanics, while not always showing the highest success rates, generally were closer to the correct age than other ancestry groups. The overall success rate for Ubelaker (1989 ) was 80.00% for both observers, while the London Atlas was significantly lower at approximately 21.79–23.28%. Accuracy rates did not differ significantly between ancestry groups, though patterns were evident regarding under‐ or over‐estimation of age. Discussion: The present study demonstrates that incorrect age estimations were typically still within 1.5 years of the actual age. Ubelaker (1989 ) had higher rates of success due to broader age ranges. The results suggest that though accuracy rates did not significantly differ, different developmental rates may affect age estimates and population‐specific standards should be considered for known‐ancestry individuals, while aging standards constructed from a diverse sample should be utilized for unknown‐ancestry cases.